The abundances of heavy elements in the atmosphere of hyades giant 6 Tauri - Gopka, V. F. (Одеські астрономічні публікації, 2017)
Comparison of synthetic spectrum of the б Tauri photosphere and high quality spectral atlas of this star permit us to identify absorption lines of iron and heavy elements Z ≥ 30 in the observed spectrum. The abundances of 16 heavy elements in the atmosphere б Tauri were determined with the differential method of spectrum synthesis. All the abundances are near solar values.